JAPANESE LANGUAGE STUDENTSâ€™ PERCEPTION OF USING ANIME AS A TEACHING TOOL - Chan, Yee-Han; Wong, Ngan-Ling; Ng, Lee-Luan (Indonesian Journal of Applied Linguistics, 2017)
Studies showed that interest in anime motivates students to learn the Japanese language and culture (Manion, 2005; Fukunaga, 2006; William, 2006). However, little has been written about the practical use of anime in a Japanese language classroom. By employing the method of classroom research, this study will try to narrow the gap between theory and practice of using anime as a teaching tool in the Japanese language classroom. This qualitative study will focus on discussing what the participants think about the use of anime as a teaching tool. A course named â€œLearning Japanese language and Culture through Animeâ€ was planned and conducted in a public university in Malaysia. During the administration of the course, the data were collected via the participantsâ€™ learning diaries at 7 intervals and a group interview at the end of the semester. The findings presented from the data analysis on the participants' perception of the use of anime as a teaching tool include motivation, language and cultural awareness, critical thinking, sense of prejudice, and stereotypes. The findings reveal that giving a place for anime in the Japanese language classroom is like opening a new door for educators to connect with the students and deepen understanding about the studentsâ€™ learning experiences of using anime as a language and culture learning tool. This is important to provide insightful ideas to the Japanese language educators regarding the option of using anime as a teaching tool.